The potential of transformative learning for sustainability transitions: moving beyond formal learning environments - Singer-Brodowski, Mandy (Environment, development and sustainability, 2025)
Transformative learning has become one of the most prominent learning theory in regard to sustainable development. It holds enormous potential for explaining and accompanying learning processes related to processes of transformation for sustainability, especially due to its emphasis on changing meaning perspectives in discussions with others in spaces free of coercion. In addition, it inspires learners and educators to pay particular attention to emotional challenges when they engage in critical thinking. This theoretical paper explores the potential of transformative learning theory by examining informal learning environments where people do not explicitly intend to learn but learning happens en passant or incidentally. It shows the ability of transformative learning theory to explain what can happen on the level of individual learning, organizational learning, learning in multi-professional networks, and learning in transdisciplinary or transformative research cooperation processes. Based on this analysis, recommendations can be derived to stimulate, enable, and accompany transformative learning processes for sustainability.